2015
DOI: 10.1016/j.joca.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence on risk factors for knee osteoarthritis in older adults: a systematic review and meta-analysis

Abstract: Osteoarthritis (OA) is a leading cause of pain and disability and leads to a reduced quality of life. The aim was to determine the current evidence on risk factors for onset of knee pain/OA in those aged 50 and over. A systematic review and meta-analysis was conducted of cohort studies for risk factors for the onset of knee pain. Two authors screened abstracts and papers and completed data extraction. Where possible, pooled odds ratios (OR) were calculated via random effects meta-analysis and population attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
560
12
34

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 737 publications
(628 citation statements)
references
References 52 publications
22
560
12
34
Order By: Relevance
“…In addition, metabolic factors (hypertension, type 2 diabetes mellitus, impaired fasting glucose [IFG], dyslipidemia, and lipid‐lowering drugs) and nodal OA, which have been implicated in OA etiology at other joints, were investigated 19, 20, 21, 22. Demographic data (age, sex, occupation), along with the presence of hip pain and knee pain in the last year, wearing of high‐heeled and narrow‐toed footwear between the ages of 20 and 49 years, 12, and intermittent claudication determined from the Edinburgh Claudication Questionnaire 23, were collected in the health survey questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, metabolic factors (hypertension, type 2 diabetes mellitus, impaired fasting glucose [IFG], dyslipidemia, and lipid‐lowering drugs) and nodal OA, which have been implicated in OA etiology at other joints, were investigated 19, 20, 21, 22. Demographic data (age, sex, occupation), along with the presence of hip pain and knee pain in the last year, wearing of high‐heeled and narrow‐toed footwear between the ages of 20 and 49 years, 12, and intermittent claudication determined from the Edinburgh Claudication Questionnaire 23, were collected in the health survey questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…10 All participants in this study are accidentally women, which is concomittant with the epidemiology data that women have a higher risk of developing OA compared to men. 7 The BMI mean for subjects in this study was 27.34 kg/m 2 with the lowest BMI of 16.01 kg/m 2 and the highest BMI was 37.65 kg/m 2 . Most subjects in this study was overweight (66.67%).…”
Section: Discussionmentioning
confidence: 57%
“…Knee OA risk is increasing in women after menopause due to hormonal fluctuations, sedentary lifestyle, and fat-rich food consumption that contribute to weight gain. 7 Weight loss in patients with knee OA should be managed through an exercise regimen in order to restore or increase the muscle mass.…”
Section: Introductionmentioning
confidence: 99%
“…PAF for other countries ranged from 43% for Australia to 8% for China, depending on obesity prevalence. Silverwood et al (27) estimated PAF for knee OA in the UK at 25%, whereas Kearns et al (28) found PAF for any OA in Ireland to be 20%. Estimates of PAF may vary due to differences in the relative risk of OA for a unit change in BMI across published studies.…”
Section: Discussionmentioning
confidence: 99%